Karakteristik Iket Sunda di Bandung dan Sumedang Periode Tahun 1968-2006 - Suciati Suciati (ITB Journal Publisher, LPPM ITB, 2008)
The study discusses the design of Iket Sunda as it is related to the life of Sundanese people and their associated culture. Iket is a type of traditional head-attire of Sunda, in which through its use we may grasp the function and status of those who wears it. Unfortunately, the use of traditional iket Sunda is no longer common and no one seems to wear it in daily basis. Yet, iket Sunda carries more than just fashion, as it also represent distinct identity amongst diverse ethnic cultures of Indonesia. This study exposes the knowledge behind iket Sunda, from the embedded aesthetic values, the associated behavior of the people who wears it, and its inter-related historical background. To address the purpose, this study applied qualitative approach based on cultural transformation theory, in order to understand the undergone changes that may relate to the design of iket-Sunda. Results indicate that iket Sunda is not completely washed out of use in today's living, as a small group of Sundanese societies in Bandung and Sumedang still wear it on a daily basis. However, some Sundanese people only wear it as part of complete traditional attire in certain events, including dance costumes and other performance activities, therefore most are not aware of the various styles of iket-Sunda. Study found that through times, iket Sunda has undergone changes on the shape, use of clothes, size, decorations, colors, and way of wearing. As rare as it may be, iket Sunda represents the true identity of Sundanese people and their associated culture.